(untitled) (Journal of Universal Science Research, 2023)
The article provides information on the balance of existing land areas in a number of developed countries, including Uzbekistan,on the implementation of scientific research work on this subject, the techniques and technologies used, a new device, its installation, application and positive results to be obtained, as well as scientific research work on finding a solution to this problem.